Socio-cognitive and personal characteristics of young offenders: a field study - Carmen Borrás (Universidad de San Buenaventura, 2017)
Adolescence is characterized by a prevalence of risk-taking and the challenging of social norms which appears to bear relation to personal abilities and social cognitive deficits. With the aim of understanding this relationship a comparative study was undertaken with two groups of adolescents, one belonging to the standard population and one comprising young people who have been subject to social reform. In order to evaluate the variables involved, use was made of the Questionnaire for Evaluating Problems of Adolescents (Q-PAD). The results obtained show that both groups display significant differences in all the variables presented by the Questionnaire, with the exception of those relating to bodily dissatisfaction and conflict. Succinctly, it emerged that the young offenders presented emotional and interpersonal problems and were at risk of psychological disturbance. They demonstrated uncertainty about the future, liability to substance abuse and issues of self-esteem. These results suggest the need for programmes of prevention and intervention which specifically take into account these variables.